Challenges in diagnostic research of multisystem inflammatory syndrome in children associated with COVID-19 in combination with the early stage of Epstein-Barr virus infection - Е. А. Kashirina; N. M. Yugay; O. B. Karabanova; L. V. Markina; E. V. Babenko; S. G. Zagidullina; O. A. Lomakina; N. I. Kolganova; A. A. Glazyrina; Yu. Yu. Novikova; A. E. Andzhel; Yu. V. Romanova; et al. (LLC "Diagnostics and Vaccines", 2022)
Multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19 is a rare life-threatening immunopathological complication of COVID-19 that develops 1-6 weeks after the acute coronavirus infection. MIS-C is characterized by fever and multiorgan inflammation.We present a clinical case of a 10-year-old boy with skin lesions at the onset of MIS-C (erythematous malar rash, lacelike rash on the trunk and extremities and petechiae) with macrophage activation syndrome development and the early stage of primary Epstein-Barr virus infection (EBV infection) which required the exclusion of X-linked lymphoproliferative disease.This clinical case demonstrates the complexity of diagnosis in MIS-C with skin manifestations at the onset of the disease, especially with concurrent activation of other infections, particularly EBV infection.